Adherence to Published Antimicrobial Prophylaxis Guidelines for Wounded Service Members in the Ongoing Conflicts in Southwest Asia. Issue 3 (1st March 2014) - Lloyd, Bradley A.; Weintrob, Amy C.; Hinkle, Mary K.; Fortuna, Gerald R.; Murray, Clinton K.; Bradley, William; Millar, Eugene V.; Shaikh, Faraz; Vanderzant, Kristen; Gregg, Stacie; Lloyd, Gina; Stevens, Julie; et al.
ABSTRACT: In 2008, a clinical practice guideline (CPG) was developed for the prevention of infections among military personnel with combat-related injuries. Our analysis expands on a prior 6-month evaluation and assesses CPG adherence with respect to antimicrobial prophylaxis for U.S. combat casualties medically evacuated to Landstuhl Regional Medical Center over a 1-year period (June 2009 through May 2010), with an eventual goal of continuously monitoring CPG adherence and measuring outcomes as a function of compliance. We classified adherence to the CPG as receipt of recommended antimicrobials within 48 hours of injury. A total of 1106 military personnel eligible for CPG assessment were identified and 74% received antimicrobial prophylaxis. Overall, CPG compliance within 48 hours of injury was 75%. Lack of antimicrobial prophylaxis contributed 2 to 22% to noncompliance varying by injury category, whereas receipt of antibiotics other than preferred was 11 to 30%. For extremity injuries, antimicrobial prophylaxis adherence was 60 to 83%, whereas it was 80% for closed injuries and 68% for penetrating abdominal injuries. Overall, the results of our analysis suggest an ongoing need to improve adherence, monitor CPG compliance, and assess effectiveness.